Kadar radikal superoksid (O2-), nitric oxide (NO) dan asupan lemak pada pasien hipertensi dan tidak hipertensi - Astutik, Pudji; Adriani, Merryana; Wirjatmadi, Bambang (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2014)
Background: Hypertension closely related to impaired endothelial dependent vasodilation due to a decline in theavailability of nitric oksid (NO) and high fat intake, decreased Nitric Oksid caused due to increased levels ofsuperoksid.Objective: to analyze the differences in the levels of Superoksid Radical (O2-), Nitric oxide (N0) and fat intake inpatients with hypertension and not hypertension .Methods: this research is cross sectional, research amount sampelnya taken at random. 24 respondent patientsconsisting of 12 cases control, and 12 the age of 65 40- tahun.pengambilan samples conducted in outpatient installationregional general hospital Sidoarjo. Done bseline superoksid levels, nitric oxide and recall fat intake.Results: the average rate of Superoksid respondents not hypertension 0.250± 0, 034U/mL, 0,314± 056U/mLhypertension, Average levels of Nitric oksid respondents not hypertension 116,083± 46,962μ M, of which hypertension72,333± 40,51μ M, average consumption of fat respondents not hypertension 41,65± 8, 32gram, 51,52± 6,74gramhypertension . Based on the test results the difference against Superoksid levels of both research groups using a t-testtwo samples are free retrieved the value p < 0,05 (p = 0,004), NO content retrieved the value p < 0,05 (p = 0,023), fatintake obtained the value of p < 0,05 (p = 0,004) which means that there is a meaningful difference in the levels ofSuperoksid, Nitric oxide and the level of fat intake among respondents with no hypertension and hypertension.Conclusion: there is a radical difference in the levels of Superoksid, NO (Nitric Oxide) and fat intake in patients withhypertension and not hypertension.